2010
DOI: 10.1111/j.1469-7580.2010.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth and exercise on composition, structural maturation and appearance of osteoarthritis in articular cartilage of hamsters

Abstract: Articular cartilage composition and structure are maintained and remodeled by chondrocytes under the influence of loading. Exercise-induced changes in the composition, structure, mechanical properties and tissue integrity of growing and aging hamster articular cartilage were investigated. Articular cartilage samples (n = 191) were harvested from the proximal tibiae of hamsters aged 1, 3, 6, 12 and 15 months. The hamsters were divided into runners and controls. The runners had free access to a running wheel bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 47 publications
3
40
1
Order By: Relevance
“…Lifelong moderate and non-voluntary running exercise of C57BL mice between the ages of 2 and 18 months was shown to increase the incidence and severity of OA [19]. A similar trend was observed in hamsters with voluntary exercise only at a young age [8], but this phenomenon was more clearly evident in rats [24]. Earlier studies on the effects on lifelong exercise on growth and maturation have focused mainly on studying the incidence OA, and have not examined the compositional and structural changes in AC.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Lifelong moderate and non-voluntary running exercise of C57BL mice between the ages of 2 and 18 months was shown to increase the incidence and severity of OA [19]. A similar trend was observed in hamsters with voluntary exercise only at a young age [8], but this phenomenon was more clearly evident in rats [24]. Earlier studies on the effects on lifelong exercise on growth and maturation have focused mainly on studying the incidence OA, and have not examined the compositional and structural changes in AC.…”
Section: Introductionsupporting
confidence: 70%
“…More specifically, in OA, the PGs of the superficial zone experience loss and the collagen fibril network in the surface-most cartilage becomes progressively disorganized [14][15][16][17]. Earlier findings have indicated that exercise may protect from OA, make the joint more prone to OA, or have no effect on the incidence of OA [8,[18][19][20][21][22]. Part of this controversy may be explained by variations in the amount of exercise and its duration, as well as the site investigated in the joint [16].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations